Early Hypocalcemia in Pediatric Major Trauma: A Retrospective Cohort Study. Issue 10 (12th October 2022) - Gimelraikh, Yulia; Berant, Ron; Stein, Michael; Berzon, Baruch; Epstein, Danny; Samuel, Nir
Abstract : Objective: Early hypocalcemia (EH) is common in adult major trauma patients and has been associated with coagulopathy, shock, increased transfusion requirements, and mortality. The incidence of EH in pediatric severe trauma has not been investigated. We aimed to explore the incidence of EH among severely injured children. Methods: We conducted a retrospective cohort study at a tertiary children's hospital and a level 1 pediatric trauma center. We extracted the medical records of all pediatric major trauma patients, defined as an age less than 18 years and an Injury Severity Score (ISS) greater than 15, admitted after trauma team activation from January 2010 to December 2020. The primary outcome was the presence of EH. Patients were classified into 3 groups: severe hypocalcemia (ionized calcium [iCa] <1 mmol/L), hypocalcemia (1 < iCa < 1.16 mmol/L), and normal calcium (iCa ≥1.16 mmol/L). Results: During the study period, 5126 children were hospitalized because of trauma. One hundred eleven children met the inclusion criteria. The median age was 11 years (interquartile range [IQR], 4–15), and 78.4% (87) were male. The median ISS was 21 (IQR, 17–27). Hypocalcemia was found in 19.8% (22) and severe hypocalcemia in 2.7% (3) of the patients. Although not statistically significant, hypocalcemic pediatric trauma patients had higher ISS (25.5 [IQR, 17–29] vs 21 [IQR, 17–26], P = 0.39), lower Glasgow Coma Scale (11 [IQR, 3–15] vs 13 [IQR, 7–15], P = 0.24), a more prolonged hospital stay (8 days [IQR, 2–16] vs 6 days [IQR, 3–13], P = 0.36), a more frequent need for blood products (27.3% vs 20.2%, P = 0.74), and higher mortality rates (9.1% vs 1.1%, P = 0.18) compared with normocalcemic patients. Conclusions: Our data suggest that in the setting of major trauma, EH is less frequent in children than previously reported in adults. Our preliminary data suggest that pediatric patients with EH may be at risk of increased morbidity and mortality compared with children with normal admission iCa requiring further studies.